The Effects of Gender and Reading Mediums on Reading Comprehension - Nero, Corrin Alicia; Norehan, Zulkiply (UNIMAS Publisher, 2020)
The present study examined the effects of gender and different types of reading mediums on reading comprehension among students. Forty undergraduates were asked to read four psychopathology texts (two digital texts and two print texts). Results showed thatthere was no significant difference in reading comprehension between gender. However, the mean scores obtained by females were slightly higher than males. Results also showed that reading comprehension between the two groups (print versus digital) was notsignificantly different. Nevertheless, the mean scores revealed that participants’ performance in print reading was slightly better than digital reading, suggesting that participants may have benefited a bit more from print reading. The present findings shed further light on the effects of digital reading and print reading on reading comprehension.